Synthesis and evaluation of a 18F-labeled diarylpyrazole glycoconjugate for the imaging of NTS1-positive tumors - Lang, Christopher; Maschauer, Simone; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (Journal of Medicinal Chemistry, 2013)
Aiming to image NTS1 overexpressing tumors, the diarylpyrazole glycoconjugate 8, derived from the potent NTS1 antagonist SR142948A, was synthesized taking advantage of the palladium-catalyzed aminocarbonylation reaction. The glycoconjugate 8 displayed excellent affinity and selectivity toward NTS1. Radiosynthesis proceeded straightforwardly, obtaining [ F]8 with excellent stability and highly beneficial biodistribution in vivo as demonstrated by PET imaging in HT29 tumor-bearing nude mice. Thus, the tracer [F]8 represents a highly promising candidate for PET imaging of NTS1-positive tumors. © 2013 American Chemical Society.